2021
DOI: 10.5336/jcog.2021-85924
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy and Safety of Gynomax® XL Vaginal Ovule in the Treatment of Common Vaginal Infections: A Single-Arm Clinical Trial, Gyno-Türk

Abstract: The objective of this study was to evaluate the efficacy, safety, and tolerability of Gynomax ® XL vaginal ovule in the treatment of bacterial vaginosis (BV), candidal vulvovaginitis (CVV), trichomonal vaginitis (TV), and mixed vaginal infections (MVI). Material and Methods: A total of 98 women diagnosed clinically with BV, CVV, TV, or MVI have completed this study. Patients were given Gynomax ® XL for 3 consecutive days, and approximately 10 (+/-5) days after the treatment, a follow-up visit was conducted. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 17 publications
2
2
1
Order By: Relevance
“…While our study results generally align with these findings, our tenth-day cure rate was slightly higher (95.5% vs 80.6%) than what was reported. Clinical recovery rates in Gyno-Türk study [13], sharing a similar study design but being a single-arm study, were comparable to our study (95.5% vs 96.9%).…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…While our study results generally align with these findings, our tenth-day cure rate was slightly higher (95.5% vs 80.6%) than what was reported. Clinical recovery rates in Gyno-Türk study [13], sharing a similar study design but being a single-arm study, were comparable to our study (95.5% vs 96.9%).…”
Section: Discussionsupporting
confidence: 84%
“…AE distribution was similar across all three treatment arms. In comparison with the Gyno-Türk study, where 14.6% of the patients experienced AEs following vaginal treatment with the comparator medication [13], our larger study observed a lower percentage (11.4%) in that arm.…”
Section: Discussioncontrasting
confidence: 79%
See 3 more Smart Citations